2006
DOI: 10.1038/sj.jp.7211545
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of intrahepatic cholestasis of pregnancy in a primarily Latina Los Angeles population

Abstract: Objective: To establish the prevalence of intrahepatic cholestasis of pregnancy (ICP) in a primarily Latina population in the United States.Study design: Over a period of 16 months, a convenience sample of subjects admitted to labor and delivery in the third trimester was enrolled. Each subject completed a questionnaire rating their severity of pruritus on a numeric scale of 1 to 10. Serum was analyzed via radioimmunoassay for total bile acid concentration. ICP was defined as pruritus score >4 and a total seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 19 publications
(24 reference statements)
6
84
0
3
Order By: Relevance
“…IHCP is the most common liver disease in pregnancy with prevalence ranging between 0.3 and 5.6% (36)(37)(38). IHCP presents in the second and third trimesters as persistent pruritus, typically involving the palms and soles as well as the rest of the body, with elevated bile acid levels, and resolves with delivery.…”
Section: Second and Third Trimestermentioning
confidence: 99%
“…IHCP is the most common liver disease in pregnancy with prevalence ranging between 0.3 and 5.6% (36)(37)(38). IHCP presents in the second and third trimesters as persistent pruritus, typically involving the palms and soles as well as the rest of the body, with elevated bile acid levels, and resolves with delivery.…”
Section: Second and Third Trimestermentioning
confidence: 99%
“…1-5 A prevalence of 5.6% of ICP has been reported in a Los Angeles population that was primarily Latina. 6 Adverse fetal outcomes associated with ICP reported in literature include spontaneous and iatrogenic preterm birth, fetal distress, respiratory distress syndrome, meconium staining, neonatal intensive care unit admission, and stillbirth. 4,7-10 Fetal mortality is reported up to 1.5-7% but as high as 20% in some studies.…”
Section: Methodsmentioning
confidence: 99%
“…However, the low prevalence rate in the United States can be misleading. A recent study examining the prevalence of IHCP in a primarily Latino Los Angeles population found that the overall prevalence of IHCP in this population was much higher (5.6%) [2]. The authors attributed the high prevalence to the ethnic background of the patients they served, 93% (316 of 340) of whom identified themselves as Latino in origin.…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 98%
“…Nevertheless, there are clear ethnic and racial differences. The disease has been described worldwide; however, the highest incidence is found in Chile and Bolivia, where the prevalence has been reported from 4% to 22% [2]. In Scandinavian countries (where it was first described), the incidence is moderate, between 1% and 2%.…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%